Building a Transdisciplinary Team to Prevent Intimate Partner Homicide: A Research Note - Pizarro, Jesenia M. (Homicide studies, 2023)
Intimate partner violence (IPV) and intimate partner homicide (IPH) are complex global problems. Transdisciplinary research approaches offer the potential to increase the understanding of these events and inform best practices for prevention. To encourage scholars to adopt transdisciplinary practices when investigating multifaceted problems, this note employs a case study approach to detail one such effort—The Preventing and Assessing Intimate Partner Homicide Risk (PAIR) Studies. The goal of the PAIR Studies is to improve the understanding of IPH to inform the development of best practices for prevention. The note concludes with a discussion of the benefits of transdisciplinary approaches.